Late childhood interpersonal callousness and conduct problem trajectories interact to predict adult psychopathy - Byrd, Amy L. (The journal of child psychology and psychiatry, 2017)
Peer Reviewedhttp://deepblue.lib.umich.edu/bitstream/2027.42/135659/1/jcpp12598_am.pdfhttp://deepblue.lib.umich.edu/bitstream/2027.42/135659/2/jcpp12598.pd